A second-order factor gender-measurement invariance analysis of financial exclusion in ilorin, Nigeria - Adewale, Abideen Adeyemi (International Association of Computer Science and Information Technology (I A C S I T), 2013)
This study examines a measurement invariance of a second-order factor models of financial exclusion among micro-entrepreneurs in Ilorin, Kwara State, Nigeria. Data elicited via a survey questionnaire was analysed using both the Statistical Package for Social Sciences (SPSS) 20.0 and Amos 20.0 software. The study revealed that financial exclusion as a second order factor is indicated by debt phobia, religion, financial complacency, and affordability and eligibility first order factors. Measurement invariance was tested based on gender via a set of hierarchically structured levels: a) configural invariance, b) metric invariance of both the firstorder and second-order models, c) intercepts of both the firstorder and second-order models, and d) residuals of both the first-order and second-order models. The groups were found to be invariant across the models. Moreover, based on t-test at alpha of 0.001, the latent mean difference tests of the second order model indicates no statistically significant difference on a path by path basis along gender divides. This provides a further questioning on the focus on women of financial inclusion programmes